Two New Oxodolastane Diterpenes from the Jamaican Macroalga Canistrocarpus cervicornis - Campbell, Sanjay (Mar Drugs, 2017)
The chemical investigation of the organic extract of Canistrocarpus cervicornis, collected at Drunken Man’s Cay at Port Royal, Jamaica, has led to the isolation of two new dolastane diterpenes 4R-acetoxy-8S,9S-epoxy-14S-hydroxy-7-oxodolastane (1) and 4R-hydroxy-8S,9S-epoxy-14S-hydroxy-7-oxodolastane (2) and the previously isolated dolastane (4R,9S,14S)-4,9,14-trihydroxydolast-1(15),7-diene (3) as a major diterpene constituent. The structures of the new compounds were elucidated by extensive spectroscopic analyses. Compounds 1–3 were evaluated for their cytotoxicity against human tumor cell lines PC3 and HT29. The results revealed that the dolastane diterpenes (1–3) displayed moderate, concentration dependent, cytotoxicity.